Induced breeding of threatened Indian medium carp Puntius pulchellus - SRIDHAR, N; RAGHUNATH, M R; HEMAPRASANTH, K P; RAGHAVENDRA, C H; EKNATH, A E (The Indian Journal of Animal Sciences, 2014)
The reproductive biology of the Indian Medium Carp (Puntius pulchellus) was studied and induced breeding of the fish accomplished. Males were dark and exhibited pinkish red prominent tubercles on the snout in contrast to the plain snouted females which however, had a deep pink lateral band. The gonado somatic index observed in females indicated a prolonged spawning period. The fish was successfully induced bred for the first time using a preparation consisting of Salmon Gonadotropin Releasing Hormone Analogue. and Domperidone (0.5ml/kg body weight) followed by pituitary extract @ of 8mg/kg and 2mg/kg for females and males respectively. The larvae appeared (hatching) after 48 h with a heavily laden yolk sac which was absorbed completely after 8days. The embryonic and larval developments are discussed.